Evaluation of Lactobacillus strains for selected probiotic properties - Turková, Kristýna; Mavrič, Anja; Narat, Mojca; Rittich, Bohuslav; Spanová, Alena; Rogelj, Irena; Matijašić, Bojana Bogovič (Folia microbiologica, 2013)
Eleven strains of Lactobacillus collected in the Culture Collection of Dairy Microorganisms (CCDM) were evaluated for selected probiotic properties such as survival in gastrointestinal fluids, antimicrobial activity, and competition with non-toxigenic Escherichia coli O157:H7 for adhesion on Caco-2 cells. The viable count of lactobacilli was reduced during 3-h incubation in gastric fluid followed by 3-h incubation in intestinal fluid. All strains showed antimicrobial activity and the three most effective strains inhibited the growth of at least 16 indicator strains. Antimicrobial metabolites of seven strains active against Lactobacillus and Clostridium indicator strains were found to be sensitive to proteinase K and trypsin, which indicates their proteinaceous nature. The degree of competitive inhibition of non-toxigenic E. coli O157:H7 adhesion on the surface of Caco-2 cells was strain-dependent. A significant decrease (P < 0.05) in the number of non-toxigenic E. coli O157:H7 adhering to Caco-2 cells was observed with all lactobacilli. Three strains were selected for additional studies of antimicrobial activity, i.e., Lactobacillus gasseri CCDM 215, Lactobacillus acidophilus CCDM 149, and Lactobacillus helveticus CCDM 82.
Keywords: Caco-2 Cells; epitelové buňky; antiinfekční látky; Bacterial Adhesion; Microbial Viability; Caco-2 buňky; mikrobiální viabilita; Anti-Infective Agents; Gastric Juice; Epithelial Cells; probiotika; Escherichia coli O157; bakteriální adheze; Probiotics; Humans; žaludeční šťáva; Antibiosis; Lactobacillus; lidé; antibióza